Visibility and vulnerability: A mixed methodology approach to studying Roma individuals’ victimization experiences - Wallengren, Simon (International review of victimology, 2020)
The present study examines the prevalence and impact of victimization among a sample of Roma individuals in Malmö and Gothenburg (Sweden). The aim of the study was to examine the link between visibility and victimization, and whether the Roma community employs behavioural strategies to reduce visibility, and, finally, to analyse how such strategies affect the group. The study design combines survey data (n=610) with interviews (n=30). The findings suggest that visibility is an important risk factor for victimization and that the study participants’ attempt to conceal their ethnicity affects them negatively both at an individual and a community level. The discussion concludes by presenting a number of policy implications.